2022
DOI: 10.1111/liv.15466
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut microbiome and primary liver cancer: A two‐sample Mendelian randomization and case–control study

Abstract: Background and Aims: Observational epidemiology studies suggested a relationship between the gut microbiome and primary liver cancer. However, the causal relationship remains unclear because of confounding factors and reverse causality. We aimed to explore the causal role of the gut microbiome in the development of primary liver cancer, including hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC).Methods: Mendelian randomization (MR) study was conducted using summary statistics from genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…Genus_Odoribacter is positively involved in non-ribosomal peptide structures and negatively involved in the metabolism of phenylalanine and cyanoamino acids. Family_Porphyromonadaceae has been identified as a potential biomarker for CRC recurrence and patient prognosis (28); casecontrol study results showed that healthy controls had a higher relative abundance of family_Porphyromonadaceae than primary liver cancer patients (29), and combined analysis with our study confirmed its potential as a biomarker in cancer. Family_ Peptococcaceae and genus_Terrisporobacter have been lacking in studies of the human immune system, so it is possible that we found microbes that can be applied as new biomarkers for PD-1/PD-L1 therapy or precancerous diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…Genus_Odoribacter is positively involved in non-ribosomal peptide structures and negatively involved in the metabolism of phenylalanine and cyanoamino acids. Family_Porphyromonadaceae has been identified as a potential biomarker for CRC recurrence and patient prognosis (28); casecontrol study results showed that healthy controls had a higher relative abundance of family_Porphyromonadaceae than primary liver cancer patients (29), and combined analysis with our study confirmed its potential as a biomarker in cancer. Family_ Peptococcaceae and genus_Terrisporobacter have been lacking in studies of the human immune system, so it is possible that we found microbes that can be applied as new biomarkers for PD-1/PD-L1 therapy or precancerous diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…Digestive system cancers (DSCs) comprise gastrointestinal cancers (esophageal cancer, gastric cancer, small intestinal cancer, colorectal cancer) and hepatobiliary-pancreatic cancers (liver cancer, gallbladder cancer, biliary duct cancer, pancreatic cancer). In general, DSCs are the most commonly diagnosed cancers and the leading cause of cancer deaths throughout the world, as they account for > 26.4% of the new cancer cases and > 36.3% of the new cancer deaths factors for liver cancer, and the researchers further validated the ndings by a case-control study [9]. Nonetheless, the current studies did not systematically examine the relationships between gut bacteria and different DSCs.…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, recent research has highlighted the importance of the gut microbiome in response to cancer immunotherapy. A study by Ma et al in 2023 showed that the abundance of Ruminococcaceae, Porphyromonadaceae and Bacteroidetes is related to a reduced risk of liver cancer (HCC or ICC), suggesting potential importance of gut microbiome regulation for the prevention and control of liver cancer 52 . Hu et al indicated that the gut microbial metabolite acetate can modulate ILC3 function through Sox13‐dependent signaling, and the combination of PD‐1/PD‐L1 blockade with acetate administration enhances antitumor immunity in HCC mouse models 53 .…”
Section: The Regulatory Signals Of Icp In the Development Of Hccmentioning
confidence: 99%